Survey on smoking habits among seafarers - Grappasonni, Iolanda (Acta Biomed, 2019)
Background: Populations living in stressful environments experience higher mortality from lung cancer and chronic diseases. Work-related stress was identified as important determinant of smoking together to health problems caused by a incorrect lifestyles. Aim of the work was to analyze tobacco smoking addiction in seafarers working on merchant ships. Only a few studies are available on this topic. Methods: The survey was conducted using an anonymous questionnaire. The total number of questionnaires filled-in was 1478, out of 2000 distributed (response rate 73.9 %). Results: About half of the sample (55.07%) has never smoked, the 28.96% is currently a smoker, while 15.97% of responders belong to the category of ex-smokers. Analysis of the number of cigarettes smoked every day based on the rank shows that captains and officers smoke more cigarettes than the crew members who smoke 10 cigarettes maximum per day. Analysis of the level of dependence among the smokers group by the Fagerström Test for Nicotine Dependence (FTND) revealed that a 89.0% of sample has a low/very low dependence level, and only the 10.98% of the sample show a high/very high dependence. A further analysis of the results of FTND in the different age groups has shown that the 41-50 and 51-60 age groups have high dependence levels. Conclusions: Working on board is associated to a high risk for chronic, lifestyle-related diseases, due also to lifestyle behaviours. This study suggests to further investigate the presence of other risk factors such as diet, physical exercise, combined with tobacco smoking, obesity. (www.actabiomedica.it)